Dissecting the Roles of Social Capital in Farmer-to-Farmer Extension: A Review - Colby J Silvert; Willis Ochieng; Jose Perez Orozco; Ange Asanzi (Journal of International Agricultural and Extension Education, 2022)
Various types of relationships within a farmer-to-farmer (F2F) extension system can influence farmers’ access to advancement opportunities, resources, capacity building, and social and professional networks. Using a social capital theoretical lens, this review elucidates the nature of these relationships and networks to better understand how bonding, bridging, and linking social capital may be leveraged in positive and negative ways and how relationship dynamics relate to farmers’ power, opportunities, and gender equity. This research demonstrates that all three types of social capital are instrumental but play different and often complementary roles in F2F extension. While bonding social capital is crucial for social cohesion, too few connections to outside actors and networks may cause farmer communities to become wary and unreceptive to innovation and change. On the other hand, outside linkages without sufficient bonding social capital to build trust may lead to inequitable distribution of desirable resources and power. Our most fundamental recommendation is to use social capital conceptualizations – specifically bonding, bridging, and linking – in the design, implementation, and evaluation of F2F extension systems. Participatory mapping of social capital, using a social equity lens, could help farmer groups identify where social capital is plentiful and where it is scarce. Building awareness among diverse farmer communities about social capital dynamics, especially linked to gender, may encourage shifts in attitudes and decision-making to reduce barriers and help marginalized farmers build social capital. Finally, we recommend making host communities and farmer groups attractive to outside interests, investments, and networks, to promote development and innovation.
Keywords: extension; farmer-to-farmer; gender equity; international development; social capital